Uso de finos de carvão e esterco de galinha em solo cultivado com milho e na produção de mudas de café - Ribeiro, Paulo Henrique (2016)
The organic composts based on charcoal fines and chicken manure can improve soil fertility and plant production. The aim of this thesis was to evaluate the chemical and physical characteristics of eucalyptus fine charcoal incubated with chicken manure, th